Characteristic Associated with Perineal Rupture in Multiparous Delivery Mother - Sukmadewi, Niluh Putu Ayu; Nurilyani, Nurliyani; Sunarsih, Sunarsih; Susilawati, Susilawati (JURNAL PROTEKSI KESEHATAN, 2024)
In 2017, 566 mothers in Indonesia experienced perineal rupture, while in Lampung in 2022, there were 24 cases of bleeding triggered by perineal rupture. This study aims to identify characteristics associated with perineal rupture in multiparous mothers at PMB Midwife Ketut Dani, SST, in 2023. The research design was cross-sectional with a sample of 45 multiparous mothers, where 30 experienced perineal rupture and 15 did not. Simple random sampling was used, and data were analyzed using univariate and bivariate methods with the chi-square test. Results showed 66.7% of multiparous mothers experienced perineal rupture, while 33.3% did not. Significant factors associated with perineal rupture were maternal age (p-value 0.015) and birth spacing (p-value 0.019). However, infant birth weight (p-value 0.800) had no significant relationship with perineal rupture. This study emphasizes the importance of maternal age and birth spacing in the prevention of perineal rupture and encourages the practice of perineal massage and Kegel exercises for multiparous pregnant women.